Micromechanical properties of hydroxyapatite nanocomposites reinforced with CNTs and ZrO2. Issue 5 (1st March 2023) - Musharavati, Farayi; Jaber, Fadi; Nasor, Mohamed; Sarraf, Masoud; Nezhad, Erfan Zal; Uzun, Kaan; Ma, Ye; Bae, Sungchul; Singh, Ramesh; Chowdhury, Muhammad E.H.
Abstract: This study examined the mechanical properties, wettability, and tribology of hydroxyapatite (HA)–zirconia (ZrO2 )–carbon nanotube (CNTs) ceramic nanocomposites (with various CNT ratios (x): 1, 5, and 10 wt%). HA–ZrO2 –CNT-x powders were hydrothermally synthesized. Hot isostatic pressing (HIP) and cold isostatic pressing were used to manufacture solid and dense tablets; consolidation was performed by sintering the nanocomposites under Ar gas at 1150 °C during HIP. The microstructure and morphology of the nanocomposites were characterized via transmission electron microscopy, energy-dispersive X-ray spectroscopy, powder X-ray diffractometry, Fourier transform infrared (FTIR), and scanning electron microscopy. The effects of ZrO2 and CNTs on the mechanical characteristics of the nanocomposites were examined via nanoindentation, reciprocating wear, and Vickers hardness tests. The microhardness of HA–ZrO2 –CNT-1% and HA–ZrO2 –CNT-5% increased by 36.8% and 66.67%, respectively, compared with that of pure HA. The nanohardness of the HA–ZrO2 –CNT-1%, HA–ZrO2 –CNT-5%, and HA–ZrO2 –CNT-10% samples was 8.3, 9.65, and 8.02 Gpa, and the corresponding elastic modulus was 83.72, 114.34, and 89.27 GPa, respectively. Both of these parameters were higher than those of pure HA. However, in the nanocomposite reinforced with 10% CNT, as opposed to those with lower CNT ratios, their values were lower. Additionally, HA–ZrO2 –CNT-10% was the most hydrophilic nanocomposite synthesized in this study with a contact angle of 48.8°.